Improving safety design for gas pipeline installation via horizontal directional drilling: a pipe stress analysis approach - Santoso, Mochamad Yusuf; Khairiansyah, Mades Darul; Hernasa, Raya Fitrian (Jurnal Polimesin, 2024)
Horizontal Directional Drilling (HDD) has today emerged as a significant and efficient Horizontal Directional Drilling (HDD) has today emerged as a significant and efficient technique for installing pipelines for a variety of purposes, including the production of oil, natural gas, water, sewer, electrical, and telecommunications. Due to the complexity of the technology and the intricate interplay of numerous processes, the safety risks associated with process uncertainty are substantial. However, risk analysis for HDD projects is generally done using qualitative methods. One of the most common factors used for HDD risk assessment is Pipe Stress Analysis (PSA). In this article, a combination of material evaluation and PSA for HDD safety design is suggested to improve the risk analysis. The evaluation will commence with an assessment of the material, followed by an examination of the wall thickness. Subsequently, an analysis of HDD design and pipe stress will be conducted. Using 10-inch API 5L Gr. B pipe, the safety design was successfully tested for a gas pipe project. When using HDD, a natural bend value of no less than 415.3 meters must have a horizontal length of 168 meters. According to the curvature, the length of the entire pipe is 169.03 meters. The combined installation stress was less than 1, while the combined operation stress was 114.87 MPa. These two values met the criteria specified in the standard. Overall, those steps were able to ensure that the HDD installation design is safe for construction.